Peran Guru PAI Dalam Gerakan Literasi Di Madrasah Ibtidaiyah Negeri Kota Banda Aceh - Ismaidar M. Yacob; M. Afif Zamroni; Warti'ah Warti'ah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research examines the role of Islamic Religious Education (PAI) teachers in implementing the Literacy Movement in MIN 1 and MIN 11 Banda Aceh City. The aim is to identify the strategies and methods PAI teachers apply in fostering students' basic literacy, explore supporting and inhibiting factors in implementing the literacy movement, and formulate practical recommendations for stakeholders to increase the effectiveness of the literacy movement in madrasas. This research uses a descriptive qualitative approach with the type of field research. Data collection was carried out through participant observation, unstructured interviews and documentation. The research results show that the role of PAI teachers is very important in the literacy movement, including educators, teachers, inspirers, initiators, motivators, facilitators, class managers, mediators and evaluators. Implementing the literacy movement for students is carried out through three stages: habituation, development and learning. Activities include library visits, morning reading, building a physical environment rich in literacy, writing works, and learning outside the classroom. This research contributes to the development of educational science, especially in Islamic religious education and literacy, by integrating religious aspects to foster students' basic literacy.